Vitamin D Levels in Infants With Biliary Atresia: Pre- and Post-Kasai Portoenterostomy. Issue 5 (May 2016) - Ng, Jessica; Paul, Anu; Wright, Naomi; Hadzic, Nedim; Davenport, Mark
ABSTRACT: Objectives: Infants with biliary atresia (BA) are at high risk of vitamin D deficiency. We aimed to determine the prevalence and factors influencing vitamin D levels at presentation and post-Kasai portoenterostomy (KPE). Methods: Single-centre retrospective review of infants with BA who underwent KPE. Pre- and postoperatively 25-hydroxyvitamin D (25-OHVD), liver and bone biochemistry data were collected. 25-OHVD levels <10 and 10 to 20 ng/mL were defined as vitamin D "deficiency" and "insufficiency, " respectively. Results: One hundred twenty-nine infants with BA (isolated n = 101, developmental n = 28, and white n = 79; non-white n = 50) were included in this study. At presentation, 75 of 92 (81%) were vitamin D deficient and only 1 infant had a level >20 ng/mL. Median 25-OHVD levels were 5(2–23), 17(2–72), 15(2–80), 17(2–69), and 23(2–98) ng/mL at pre-KPE, 1, 4, 6, and 12 months postoperation. There was no difference in 25-OHVD levels between the isolated and developmental groups with BA. Pre-KPE, white infants had significantly higher levels than non-white infants (6[2–23] vs 3[2–14] ng/mL, P = 0.01). Post-KPE 25-OHVD levels correlated well with liver and bone biochemical variables (eg, at 6 months: bilirubin r s = −0.34; P < 0.001, alkaline phosphatase r s = −0.46; P < 0.00001, and phosphate r s = 0.49; P < 0.00001). Conclusions: 25-OHVD deficiency is invariable at presentation in infants with BA, irrespective of its likely aetiology, and is more severe in non-white infants. Despite routine parenteral and enteral supplementation, low 25-OHVD levels persist post KPE especially in icteric infants. More aggressive vitamin D supplementation and monitoring in this population is paramount.